2016
DOI: 10.15761/ifnm.1000164
|View full text |Cite
|
Sign up to set email alerts
|

Leaching and in vitro bio accessibility of aluminium from different teas

Abstract: and the risk of Al, it is important to evaluate total Al content in tea, the leaching of Al from the tea, and the bio-accessibility of Al from its infusion after digestion at the same time. It is also necessary to compare the difference of total Al contents in green tea, black tea, and oolong tea, of the Al leaching from these teas, and of the bio-accessibility of Al from their infusions because green tea, black tea, and oolong tea were processed with different manufacturing processed, and different manufactur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Despite high concentrations of Al in infusions of analyzed teas, it was found that only a small part of this metal was available for absorption in the gastrointestinal tract. These results were in good agreement with results of studies undertaken by other authors for infusions of different BTs and GTs [22,23,32,33].…”
Section: Bioaccessibility Of Metals From Black and Green Tea Infusionssupporting
confidence: 92%
See 1 more Smart Citation
“…Despite high concentrations of Al in infusions of analyzed teas, it was found that only a small part of this metal was available for absorption in the gastrointestinal tract. These results were in good agreement with results of studies undertaken by other authors for infusions of different BTs and GTs [22,23,32,33].…”
Section: Bioaccessibility Of Metals From Black and Green Tea Infusionssupporting
confidence: 92%
“…Resulted sample solutions were diluted (1:1), acidified with HNO 3 to 0.11 mol L −1 , and measured by ICP OES. Lin and Yang [23] determined bioavailability of Al from infusions of three teas (GT, BT, and oolong tea), but without membrane ultrafiltration. Samples of infusions after in vitro GID were centrifuged, and their supernatants were analyzed by FAAS.…”
Section: Introductionmentioning
confidence: 99%